Dialectology Landscape: Duano Sea Tribe Communication at Jambi Province - Rozelin, Diana; Zurnelli, Netti; Fauzan, Umar (Universitas Sanata Dharma, 2024)
Duano language in Sabak and Tungkal is included into the extinct language category. One way to avoid language extinction is through language revitalization or language documentation. The purpose of this research is to ascertain and explain the proto language and the kinship of Duano tribe in Sabak and Tungkal through dialectology. Then, language documentation is carried out to look at all related aspects from cognate to morpheme positioning. The writers used Proto Malayic from Adelaar (1992) as IPD instrument, The data sources are Duano language from Sabak and Tungkal regencies spoken by 10 respondents. This is a qualitative study. The data were collected through interview, note-taking, recording, and documentation. Then, they were analyzed comparatively. This research found 920 zero data, 510 lexical differences data, 1210 cognate, and 570 phonological differences data. This showed that almost 50% of the data has zero difference, which means they have the same vocabulary. Then, phonological difference is 7.01% indicating that the two languages are different Speech. Meanwhile, lexical difference is 35.29% implying that the two are different subdialects, The relationship between the two regions is very close., the number of vocabularies that belong to vocabulary shift was higher than the vocabulary maintenance. This means that language extinction is very high, especially in the Tungkal area.